THE IMPORTANCE AND POSSIBILITIES OF DISTANCE EDUCATION IN THE EDUCATIONAL PROCESS - Axmadjonova, Yorqinoy; Axmadjonova, Umida (MMIT Proceedings, 2023)
Today, the teacher must breathe even with the times, despite the fact that he is a connoisseur of his profession. Our young people today are curious, able to use new technologies very well. To interest them in the lesson, innovative technologies in the course of the lesson, as well as an interesting organization of the lesson using interactive techniques, requires a lot of responsibility from the teacher. Today's modern teacher should be able to apply information communication technologies (ICT) in his lesson. The organization of the course process on the basis of innovative technologies will help to make the course process interesting, active and quickly master the course. Therefore, nowadays, interest in the application of innovative technologies, pedagogical and information technologies in the educational process, attention is gaining strength day by day, one of the reasons for this is that until then, in traditional education, students-students are taught to acquire only ready-made knowledge, while modern technologies teach them to search for the knowledge they are acquiring, independently study and analyze, In this process, the teacher creates conditions for the development, formation, acquisition and upbringing of an individual, and at the same time performs the function of stewardship, orientation.